Struktur Organisasi Kelembagaan Penanaman Modal di Kota Bandung - Dewi Gartika (Otoritas : Jurnal Ilmu Pemerintahan, 2016)
In Act No. 23 of 2014 on Regional Government, where there mention of the obligatory functions and affairs of choice, where one obligatory This is an investment, then in Government Regulation No. 38 Year 2007 on the dealings between the central government, provincial government and district / city government, a local government authority is in the field of investment, government Bandung, capital investment is obligatory and one local government authority is placed in the structure organization Bappeda Bandung is in the Investment Sector, is of course contrary to the Law No. 23 Year 2014 and Government Regulation No. 38 of 2007. This paper provides the organizational structure of institu-tional investment in the city of Bandung.Dalam Undang-Undang Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah dise-butkan mengenai urusan wajib dan urusan pilihan, dimana salah satu urusan wajib ini adalah pena-naman modal, kemudian dalam Peraturan Pemerintah Nomor 38 Tahun 2007 tentang Pembagian urusan antara pemerintah pusat, pemerintah provinsi, dan pemerintah kabupaten/kota, salah satu kewenangan pemerintah daerah adalah dalam bidang penanaman modal, di pemerintahan Kota Bandung, penanaman modal yang merupakan urusan wajib dan salah satu kewenangan pemerintah daerah ditempatkan dalam struktur organisasi Bappeda Kota Bandung yaitu pada Bidang Pena-naman Modal, ini tentu saja berseberangan dengan UU No. 32 Tahun 2004/UU No. 23 Tahun 2014 dan Peraturan Pemerintah No. 38 Tahun 2007. Artikel ini berisi tentang struktur organisasi kelem-bagaan penanaman modal di Kota Bandung.